How do you factor the expression ${y^2} + 6y - 16 = 0$?
Answer
Verified
439.5k+ views
Hint: First we will reduce the equation further if possible. Then we will try to factorise the terms in the equation. Then solve the equation by using the quadratic formula and finally evaluate the value of the variable accordingly.
Complete step-by-step solution:
We will start off by reducing any reducible terms in the equation if possible.
${y^2} + 6y - 16 = 0$
Now we will factorise the terms in the equation.
${y^2} + 6y - 16 = 0$
Now we will try to factorise by using the quadratic formula which is given by $x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}$
To substitute the values, we first compare and evaluate the values from the general form of quadratic equation. the general form of quadratic equation is given by $a{x^2} + bx + c = 0$.
When we compare the terms, we get the values as,
$
a = 1 \\
b = 6 \\
c = - 16 \\
$
Now substitute all these values in the quadratic formula, to evaluate the value of the variable.
\[
\Rightarrow y = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}} \\
\Rightarrow y = \dfrac{{ - (6) \pm \sqrt {{{(6)}^2} - 4(1)( - 16)} }}{{2(1)}} \\
\Rightarrow y = \dfrac{{ - (6) \pm \sqrt {(36) - 4(1)( - 16)} }}{{2(1)}} \\
\Rightarrow y = \dfrac{{ - 6 \pm \sqrt {(36) + 64} }}{2} \\
\Rightarrow y = \dfrac{{ - 6 \pm \sqrt {100} }}{2} \\
\Rightarrow y = \dfrac{{ - 6 \pm 10}}{2} \\
\Rightarrow y = - 3 \pm 5 \\
\]
Now we solve for the value $y$ separately.
So, we get the values as,
\[
\Rightarrow x = - 3 - 5 = - 8 \\
\Rightarrow x = - 3 + 5 = 2 \\
\]
Hence, the total valid solutions of the quadratic equation ${y^2} + 6y - 16 = 0$ are \[ - 8,2\].
Additional information: The quadratic formula is the formula that provides the solution to a quadratic equation. there are two ways of solving a quadratic equation instead of using the quadratic formula, such as factoring, completing the square, graphing and others.
Note: While splitting the middle term be careful. After splitting the middle term Do not solve all the equations simultaneously. Solve all the equations separately, so that you don’t miss any term of the solution. Check if the solution satisfies the original equation completely. If any term of the solution doesn’t satisfy the equation, then that term will not be considered as a part of the solution.
Complete step-by-step solution:
We will start off by reducing any reducible terms in the equation if possible.
${y^2} + 6y - 16 = 0$
Now we will factorise the terms in the equation.
${y^2} + 6y - 16 = 0$
Now we will try to factorise by using the quadratic formula which is given by $x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}$
To substitute the values, we first compare and evaluate the values from the general form of quadratic equation. the general form of quadratic equation is given by $a{x^2} + bx + c = 0$.
When we compare the terms, we get the values as,
$
a = 1 \\
b = 6 \\
c = - 16 \\
$
Now substitute all these values in the quadratic formula, to evaluate the value of the variable.
\[
\Rightarrow y = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}} \\
\Rightarrow y = \dfrac{{ - (6) \pm \sqrt {{{(6)}^2} - 4(1)( - 16)} }}{{2(1)}} \\
\Rightarrow y = \dfrac{{ - (6) \pm \sqrt {(36) - 4(1)( - 16)} }}{{2(1)}} \\
\Rightarrow y = \dfrac{{ - 6 \pm \sqrt {(36) + 64} }}{2} \\
\Rightarrow y = \dfrac{{ - 6 \pm \sqrt {100} }}{2} \\
\Rightarrow y = \dfrac{{ - 6 \pm 10}}{2} \\
\Rightarrow y = - 3 \pm 5 \\
\]
Now we solve for the value $y$ separately.
So, we get the values as,
\[
\Rightarrow x = - 3 - 5 = - 8 \\
\Rightarrow x = - 3 + 5 = 2 \\
\]
Hence, the total valid solutions of the quadratic equation ${y^2} + 6y - 16 = 0$ are \[ - 8,2\].
Additional information: The quadratic formula is the formula that provides the solution to a quadratic equation. there are two ways of solving a quadratic equation instead of using the quadratic formula, such as factoring, completing the square, graphing and others.
Note: While splitting the middle term be careful. After splitting the middle term Do not solve all the equations simultaneously. Solve all the equations separately, so that you don’t miss any term of the solution. Check if the solution satisfies the original equation completely. If any term of the solution doesn’t satisfy the equation, then that term will not be considered as a part of the solution.
Recently Updated Pages
Class 10 Question and Answer - Your Ultimate Solutions Guide
How to find how many moles are in an ion I am given class 11 chemistry CBSE
Identify how many lines of symmetry drawn are there class 8 maths CBSE
State true or false If two lines intersect and if one class 8 maths CBSE
Tina had 20m 5cm long cloth She cuts 4m 50cm lengt-class-8-maths-CBSE
Which sentence is punctuated correctly A Always ask class 8 english CBSE
Trending doubts
Assertion The planet Neptune appears blue in colour class 10 social science CBSE
The term disaster is derived from language AGreek BArabic class 10 social science CBSE
Imagine that you have the opportunity to interview class 10 english CBSE
Find the area of the minor segment of a circle of radius class 10 maths CBSE
Differentiate between natural and artificial ecosy class 10 biology CBSE
Fill the blanks with proper collective nouns 1 A of class 10 english CBSE